Physical Exercise is More Effective than HRT in Improving Lipid Profile Status in Postmenopausal Women - Ferdous, Tabassum; Jahan, Nasim; Sultana, Nayma; Akhter, Hafiza; Islam, Mohammed Montasir; Alam, Mohammed Rajeeb (Bangladesh Journal of Physiology and Pharmacology, 2014)
Disturbances of lipid profile in postmenopausal women may occur due to hormonal changes and physical inactivity which ultimately increases the risk of atherosclerosis, CHD and MI. Physical exercise may play a significant role in the management of dyslipidemia among postmenopausal women than HRT The study was carried out to compare and contrast between the effects of physical exercise and HRT in improving lipid profile status among postmenopausal women. This study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka, from 1st January, 2009 to 31st December, 2009. A total number of 90 postmenopausal women having age ranged from 50-60 years were included in the study. Among 90 postmenopausal women, 30 were performing regular physical exercise, 30 were receiving HRT and 30 were sedentary postmenopausal women without receiving HRT. Lipid profile such as TC, HDL-C, LDL-C, TG and fasting blood sugar of all the participants were estimated in Physiology laboratory, SSMC Mitford, Dhaka. The statistical analysis was done by using appropriate test as applicable. Mean serum TC, LDL-C and TG were significantly (p<0.001) higher and mean HDL-C was significantly (p<0.001) lower in sedentary postmenopausal women than those of postmenopausal women with regular physical exercise and postmenopausal women receiving HRT. Again, TC, LDL-C and TG were comparative higher in postmenopausal women receiving HRT than those of postmenopausal women with regular physical exercise and HDL-C were almost similar among these two groups of women. Conclusion: Physical exercise could be more effective than HRT in improving lipid profile status in postmenopausal women. DOI: http://dx.doi.org/10.3329/bjpp.v27i1-2.20068 Bangladesh J Physiol Pharmacol 2011; 27(1&2):9-12